Novel Quinazolinone inhibitors of ALK2 flip between alternate binding modes: Structure-activity relationship, structural characterization, Kinase profiling, and cellular proof of concept - Hudson, L; Mui, J; Vázquez, S; Carvalho, D; Williams, E; Jones, C; Bullock, A; Hoelder, S (American Chemical Society, 2018)
Structure-activity relationship and crystallographic data revealed that quinazolinone-containing fragments flip between two distinct modes of binding to activin receptor-like kinase-2 (ALK2). We explored both binding modes to discover potent inhibitors and characterized the chemical modifications that triggered the flip in binding mode. We report kinase selectivity and demonstrate that compounds of this series modulate ALK2 in cancer cells. These inhibitors are attractive starting points for the discovery of more advanced ALK2 inhibitors.